New model of health promotion and disease prevention for the 21st century. (8th July 2008) - Butler, Robert N; Miller, Richard A; Perry, Daniel; Carnes, Bruce A; Williams, T Franklin; Cassel, Christine; Brody, Jacob; Bernard, Marie A; Partridge, Linda; Kirkwood, Thomas; Martin, George M; Olshansky, S Jay
Abstract : Our susceptibility to disease increases as we grow older. Robert Butler and colleagues argue that interventions to slow down ageing could therefore have much greater benefit than those targeted at individual disease